The return of religion? The paradox of faith-based welfare provision in a secular age - Josef Hien (Max Planck Institute for the Study of Societies, 2014)
For centuries, churches were the main institutional providers of welfare in Europe before the state took over this role in the late 19th century. The influence of modernization theory meant that modern welfare state theorists increasingly regarded religion and its impact on welfare as a relic from the distant past. It was anticipated that modern, differentiated, and industrialized societies would see the decline and inevitable disappearance of religious welfare provision along with religiosity. Surprisingly, however, at the beginning of the 21st century in many modern industrialized societies, religious institutions are increasingly becoming involved in welfare provision again. The religion blind classic welfare state literature offers no explanation for this phenomenon. This present paper argues that the resurgence of faith-based welfare providers is the reversal of a phenomenon that occurred in the late 19th century when modern states started to strip religious providers of their prerogatives in welfare provision. The result was the ascendance of the modern state and the demise of religion in the late 19th century. The return of welfare to religious providers can therefore be interpreted as the beginning of the demise of the modern state. – – Jahrhundertelang war die Kirche der Hauptwohlfahrtsträger in Europa, bevor der Staat im späten 19. Jahrhundert diese Aufgabe übernahm. Der Einfluss der Modernisierungstheorie bedeutete, dass Theoretiker des modernen Wohlfahrtsstaates Religion und ihre Auswirkung auf Sozialhilfe zunehmend als ein Relikt der Vergangenheit ansahen. Man erwartete, dass in modernen, differenzierten und industrialisierten Gesellschaften der Rückgang und das unausweichliche Verschwinden kirchlicher Wohlfahrtsleistungen mit einem Zerfall an Religiosität einhergingen. Allerdings engagieren sich seit Beginn des 21. Jahrhunderts in vielen Industrienationen überraschenderweise wieder kirchliche Einrichtungen vermehrt in der Sozialfürsorge. Die klassische Literatur zum Wohlfahrtsstaat blendet die Kirche aus und liefert daher keinerlei Erklärung für dieses Phänomen. Der vorliegende Beitrag argumentiert, dass das Neuaufleben konfessioneller Wohlfahrtsanbieter das Phänomen des späten 19. Jahrhunderts wieder umkehrt, als moderne Staaten begannen, den kirchlichen Wohlfahrtsträgern die Privilegien der Sozialhilfe zu entziehen. Das Ergebnis war der Aufstieg des modernen Wohlfahrtsstaates und der Niedergang der Religion im späten 19. Jahrhundert. Das Wiedererstarken kirchlicher Wohlfahrtspflege kann daher als der Beginn des Zerfalls des modernen Staates erachtet werden.
Keywords: 300